(untitled) (Scientific journal of the Fergana State University, 2025)
This study explores the effectiveness of using movies as a pedagogical tool in English as a Foreign Language (EFL) classrooms to enhance language skills and cultural competence. By selecting appropriate films, teachers can address critical areas such as vocabulary development, pronunciation practice, and fostering critical thinking. The methodology includes criteria for choosing movies based on linguistic and cultural content. Results highlight a list of recommended films suited for different aspects of language learning. This study emphasizes the role of audiovisual materials in making EFL classrooms engaging and effective.